Evaluation of Eco-Driving Using Smart Mobile Devices - Husnjak, Siniša; Forenbacher, Ivan; Bucak, Tino (Promet - Traffic&Transportation, 2015)
The methods of measuring driving behaviour and the quality of drive in road transport are important factors in data acquisition and subsequent analysis of driving. The prevalence of smart terminal devices and cost effectiveness of On-Board Diagnostics (OBD) sensor devices provide great potential and the availability of the aforementioned technologies. This study shows the possibility of using information and communication technologies (ICT) and sensor devices for measuring the effectiveness of eco-driving. The ease of implementation of ICT elements, the accuracy of collected data and their storage for later data analysis offer a number of possibilities to use. This study shows the technical solution of the system and analysis of collected data on actual driving samples. By comparing normal and eco-driving modes, the advantage of using eco-driving modes is demonstrated through reduced fuel consumption and CO2 emissions amounting to almost 23% and 31%, respectively.